Histology and histochemistry of Broad ligaments in buffalo - BRAR, P S; SAIGAL, R P; SHARMA, R D; NANDA, A S (The Indian Journal of Animal Sciences, 2011)
Broad ligament is the only attachment of uterus with the body of the animal and can play some role in the causation of uterine torsion, a single major cause of maternal deaths in buffaloes. The present study was undertaken to study the histomorphology and histochemistry of broad ligament in buffaloes. The tissue samples for histomorphology were collected from buffalo calves delivered dead to buffaloes suffering from dystocia, multiparous non-pregnant buffaloes, early pregnant buffalo and early pregnant cow. In general the broad ligaments consisted of double serosal folds containing in between them muscles, connective tissue, nerves and blood vessels. In 0 day-old calves the fibroblasts and muscle fibres were still to be organized. The adult non-pregnant buffaloes had well developed musculature in broad ligaments. No difference in the amount of musculature was observed in right and left broad ligament or at iliac and ovarian end of the broad ligaments. However 11% non-pregnant buffaloes had exceptionally less developed muscles. On the pregnant side the broad ligaments had relatively larger muscle fascicles with frequent syncytial appearances of muscle fibres. Moreover pregnant side had relatively larger muscle fascicles. Histochemistry indicated presence of fair amount of vicinal glycol group containing carbohydrates, glycogen and neutral mucopolysaccharides in 0- day old calves, the amount of which increased with increase in age. Overall this study revealed the basic structure of broad ligaments in buffaloes and indicated their possible involvement in causation of uterine torsion.Â